Biomonitoring of atmospheric heavy metals in native lichen Xanthoria parietina around Salda Lake (Burdur – Turkey), a special environmental protection area - ÇOBANOĞLU, GÜLŞAH (My University, 2024)
Exposure to air pollutants negatively affects human health as well as the ecosystem. The target study area, Salda Lake, which is a special environmental protection area with Turkey's and the world's geoheritage and unique natural values, has become one of the tourist attraction areas in recent years. However, quantitative data on airborne trace metals in the region remain poorly described. This study focuses on the spatial distribution of atmospheric heavy metals through lichen monitoring for the first time around Salda Lake. The concentration of airborne metals accumulated in Xanthoria parietina lichen thalli samples collected from 14 sites were evaluated by multi-element analysis with Inductively Coupled Plasma-Mass Spectrometry (ICPMS). The spatial distribution of toxic metals in the region was presented as separate pollution maps. Analysis data showed that Ni, Fe, Al, Cu and Zn accumulation levels in lichen thalli were significantly higher than reference. Visitor entrance, camping areas and the road line in the west and south of the lake were among the sample areas where metal contamination was evident. Due to the prevalence of chromium mineral deposits in the region, the high level of Cr content is also quite remarkable. It was concluded that Al, Cr, Cu, Fe, Mn, Ni, Pb and Zn in the air are high enough to threaten human health and their levels vary depending on wind direction, human activities and traffic density. This study is important in terms of determining the level of air quality in this natural area and future perspectives. Keywords Airborne trace metals · Heavy metal pollution · Lichen · Biomonitoring · Atmospheric pollutants
Keywords: Yaşam Bilimleri; Çevre Biyolojisi; Mikrobiyoloji; Mikoloji; Temel Bilimler; Life Sciences; Environmental Biology; Microbiology; Mycology; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Doğa Bilimleri Genel; Biyoloji ve Biyokimya; ÇOK DİSİPLİNLİ BİLİMLER; BİYOLOJİ; MİKROBİYOLOJİ; Natural Sciences (SCI); Life Sciences (LIFE); NATURAL SCIENCES, GENERAL; BIOLOGY & BIOCHEMISTRY; MICROBIOLOGY; MULTIDISCIPLINARY SCIENCES; BIOLOGY; Mikrobiyoloji (tıbbi); İmmünoloji ve Mikrobiyoloji (çeşitli); Multidisipliner; Sağlık Bilimleri; Microbiology (medical); Immunology and Microbiology (miscellaneous); Multidisciplinary; Health Sciences; Airborne trace metals; Heavy metal pollution; Lichen; Biomonitoring; Atmospheric pollutants